Exploring the landscape of pre-service teacher leadership: A systematic literature review - Pohan, Albert Efendi; Abdul Razak, Amirul Fahmie; A. Ghani, Muhammad Faizal; Radzi, Norfariza Mohd; Alsamiri, Yasir Ayed (Universitas Riau Kepulauan, 2024)
More than ever, teachers play a larger and more significant role in society. This change in perspective has recognized pre-service teachers enrolled in teacher preparation programs as having the capacity to assume leadership roles. Despite the fact that many researchers have conducted research on pre-service teachers’ leadership, limited numbers of scholars have attempted to gather and conduct a systematic literature review on the same topic. This article seeks to address the aforementioned issues by compiling a comprehensive literature review of earlier research on pre-service teacher leadership published in English-based journals from 2020 to 2023. Through a theoretical discussion, the study synthesis aimed to uncover emerging research agendas for future research and to generate fresh perspectives on pre-service teacher leadership. The PRISMA writing standard has been used to guide this SLR's composition. Two primary databases, Web of Science and Scopus, were utilized to locate articles and relevant materials for this systematic literature review. A total of 22 articles were selected from the original 733 articles identified. Based on the content analysis done, this SLR has identified five main themes, which are